The influence of feedback on competence, motivation, vitality, and performance in a throwing task - Garcia, J.; Carcedo, R.; Castaño, J. (Research Quarterly for Exercise and Sport, 2019)
Purpose: The purpose of this work is focused on the study of the effect that feedback has on competence valuation, perceived competence, autonomous motivation, vitality, and performance in a throwing task. Method: Thirty-five college students (26 men and 9 women), without previous experience in the task, participated in this study. The students were randomly assigned to three experimental conditions (positive, negative, and lack of feedback). Results: The results of this study point out that only those who received positive feedback before the handball throwing task, in contrast to those who received negative feedback or did not receive any feedback, showed increased levels of competence valuation (p < .05, Cliff's delta effect size = -.30), perceived competence (p < .001, Cliff's delta effect size = -.77), and autonomous motivation (p < .05, Cliff's delta effect size = -.48). This group also presented higher levels of perceived competence (p < .001, Cliff's delta effect size = -.84) and subjective vitality (p < .001, Cliff's delta effect size = -.80) than the group who received negative feedback after the throwing task. Those who received positive feedback also showed a higher throwing speed at the end of task than those who received negative feedback (p < 0.001, Cliff's delta effect size = -.71) or than those who did not receive any feedback (p < .05, Cliff's delta effect size = -.56). Conclusions: Competence valuation, perceived competence, autonomous motivation, subjective vitality, and throwing speed were favorably influenced by positive feedback. These results have important implications for the training style applied by coaches.